Ultra-long-term subcutaneous EEG recordings in ten epilepsy patients: Experiences and circadian rhythms in epileptiform discharges - S.J. van Norden; K.H. Kho; A.M. Meppelink; J.J. Ardesch; M.C. Tjepkema-Cloostermans; M.J.A.M. van Putten (Epilepsy & Behavior Reports)
Recently, a subcutaneous electroencephalography (sqEEG) electrode became available, enabling ultra-long-term EEG recordings. In our PREDYct study, we aim to predict the efficacy of vagus nerve stimulation (VNS) in epilepsy patients. The study records sqEEG for up to fifteen months, including a 2–3 month period before VNS implantation. Here we report on initial patient experiences, compliance and recordings of epileptiform discharges (EDs). We included the first 10 participants from our ongoing PREDYct study. We calculated recording compliance for each patient. Patients rated their pain during electrode implantation, wearing and explantation using the visual analogue scale (VAS). Approximately two weeks of data from each patient were visually assessed and all EDs were annotated. We used these annotations to evaluate circadian rhythms in ED rate and duration and to compare seizure diaries with annotated ictal patterns. Electrode implantation and explantation were well-tolerated with a median VAS of 4 and 2, respectively. Wearing the electrode was also well-tolerated with median VAS scores of 0 and 0.5 at two and fifteen months, respectively. On average, patients wore the electrode for 441 days with an overall compliance of 27 %, resulting in 28,331 h of EEG. A circadian rhythm in ED rate was observed in three patients, while one patient exhibited a circadian rhythm in ED duration. A comparison of reported seizures and annotated ictal patterns revealed discrepancies. Ultra-long-term sqEEG is well-tolerated and has the potential to be a valuable tool for monitoring treatment. Nevertheless, it remains a challenge but crucial to attain high recording compliance.